Manipulating resistance to mungbean yellow mosaic virus in greengram (Vigna radiata L): Through CRISPR/Cas9 mediated editing of the viral genome - Talakayala, Ashwini; Mekala, Gopala Krishna; Reddy, Malireddy K.; Ankanagari, Srinivas; Garladinne, Mallikarjuna (Frontiers in Sustainable Food Systems, 2022)
Clustered regularly interspaced short palindromic repeats (CRISPR) associated protein (CRISPR/Cas9) is an adaptive immune system of bacteria to counter the impending viral pathogen attack. With persistent improvements, the CRISPR has become a versatile tool for developing molecular immunity against viruses in plants. In the current report, we utilized the Cas9 endonuclease and dual 20 bp-gRNAs targeting two different locations in single stranded DNA-A of AC1 (rep protein) and AV1 (coat protein) of mungbean yellow mosaic virus for achieving resistance in greengram. The cotyledonary nodal explants were infected with Agrobacterium strain EHA105 harboring pMDC100-Cas9 with AC1 and AV1 gRNA cassettes and generated transgenic plants. The integration of Cas9 and gRNA cassettes in the transformed plants of greengram were confirmed by PCR and Dot blot assays. Agroinfiltrated T2 transgenic lines exhibited minimal mosaic symptoms. The drastic reduction in accumulation of AC1 and AV1 was observed in T2 transformed lines. The T7EI assay indicated that AC1 fragments were edited at frequency of 46%, 32%, 20%, and AV1 at 38.15%, 40%, and 21.36% in MYMV infected greengram lines T2-6-2-3, T2-6-4-4, and T2-6-4-7, respectively. The manipulation of resistance to MYMV through editing of the pathogen genome using the CRISPR/Cas9 tool can be a powerful approach to combat viruses and develop resistance in greengram.